2016
DOI: 10.1038/nm.4047
|View full text |Cite
|
Sign up to set email alerts
|

Rps14 haploinsufficiency causes a block in erythroid differentiation mediated by S100A8 and S100A9

Abstract: Heterozygous deletion of RPS14 occurs in del(5q) MDS and has been linked to impaired erythropoiesis, characteristic of this disease subtype. We generated a murine model with conditional inactivation of Rps14 and demonstrated a p53-dependent erythroid differentiation defect with apoptosis at the transition from polychromatic to orthochromatic erythroblasts resulting in age-dependent progressive anemia, megakaryocyte dysplasia, and loss of hematopoietic stem cell (HSC) quiescence. Using quantitative proteomics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
197
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(225 citation statements)
references
References 59 publications
11
197
2
Order By: Relevance
“…[45][46][47] A recent report has shown that increased levels of S100a8 and S100a9 block erythroid differentiation in Rps14-haploinsufficient mouse model of MDS. 48 We observed erythroid differentiation defect and increased expression of S100a8 and S100a9 in Ezh2-deficient Jak2V617F (Jak2 VF/1 Ezh2 2/2 ) mice (Figures 2A and 6E). …”
Section: Discussionmentioning
confidence: 79%
“…[45][46][47] A recent report has shown that increased levels of S100a8 and S100a9 block erythroid differentiation in Rps14-haploinsufficient mouse model of MDS. 48 We observed erythroid differentiation defect and increased expression of S100a8 and S100a9 in Ezh2-deficient Jak2V617F (Jak2 VF/1 Ezh2 2/2 ) mice (Figures 2A and 6E). …”
Section: Discussionmentioning
confidence: 79%
“…Indeed, Schneider et al recently reported that Rps14 haplodeficiency induces S100A8/9 expression to direct TLR4-dependent cell-intrinsic death of polychromatic erythroblasts. 52 Comparative transcriptome analysis also shows that S100A8/9 is highly upregulated in Srsf2 P95H mutant as well as Ezh2-deleted mouse models. 53,54 Additionally, our findings that catalytically active pyroptotic ASC specks are released from the cytosol into the extracellular space suggests that specks may further reinforce bystander inflammation in the microenvironment in a non-cell-autonomous fashion.…”
Section: Discussionmentioning
confidence: 99%
“…45 TNF-a acting via S100A8 and S100A9 proteins of the innate immune system has recently been shown to be involved in the 5q-MDSs. 46 We cannot exclude the possibility that 1 or more additional factors interacting with HSP70 depending on the specific RP mutated gene may be modulating the different phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…57 An additional mechanism of p53 activation recently documented in 5q-MDSs involves the TNF-a pathway in response to secreted S100A8 and S100A9, 2 proteins of the innate immune system. 46 Finally, the decreased expression of GATA1 could also favor p53 activation. 41 Our results argue for these latter mechanisms with p53 activation being a consequence of the downregulation of GATA1 in response to HSP70 defect in RPL5 1/Mut and RPL11 1/Mut erythroid cells.…”
mentioning
confidence: 99%